(untitled) (Journal of the College of Basic Education, 2024)
This study was concerned with the rhetorical methods in the poetry of Walid al-Sarraf, a poet and doctor in the Iraqi city of Mosul and a member of the General Union of Writers in Iraq and the Arab World, since the poet possesses a collection of poetry collections that qualify him for study and university theses, including: a thesis entitled The Artistic Image in Walid’s Poetry Al-Sarraf in the College of Arts, University of Mosul, and literary and religious intertextuality in the poetry of Walid Al-Sarraf in the College of Arts and Sciences, Middle East University in the Hashemite Kingdom of Jordan, and a stylistic study in the poetry of Walid Al-Sarraf, College of Arts, Alexandria University, and it was limited to the collection of memory of the deposed king and a letter from Cain, and did not cover the collections All of them, so I chose to choose all the poet’s poetry collections and collections with a rhetorical study of the most important rhetorical methods in his poetry